Physical Activity and Well-Being of High Ability Students and Community Samples During the COVID-19 Health Alert - Valadez, María de los Dolores; Rodríguez-Naveiras, Elena; Castellanos-Simons, Doris; López-Aymes, Gabriela; Aguirre, Triana; Flores, Juan Francisco; Borges, África (Frontiers in Psychology, 2020)
The health alert caused by the COVID-19 pandemic and the lockdown have caused significant changes in people's lives. Therefore, it has been essential to study the quality of life, especially in vulnerable populations, including children and adolescents. In this work, the psychological well-being, distribution of tasks and routines, as well as the physical activity done by children and adolescents from two samples: community and high abilities, have been analyzed. The methodology used was Mixed Method Research, through a survey conducted online through social networks. The informants were the parents of the children and adolescents, 209 in the community sample and 116 in the high ability sample. The instrument used was a questionnaire implemented through Google Forms, with open and closed questions, including the Kidscreen-27 scale to measure well-being. The assessment of the adequacy of the physical activity levels was analyzed through ALCESTE. The results showed the absence of differences between students from community samples and those with high capacities in well-being and physical activity. Parents residing in Spain observed less play time in the high ability sample, and more time spent on homework, whether or not they have a diagnosis of high ability. It is concluded that these results question the misconceptions held about high ability students in terms of poorer personal adjustment and better interest in physical activities.